IMPACT OF INFORMATION TECHNOLOGY AND DIGITALIZATION ON BANKING STRATEGY PRE-COVID-19, CHALLENGES IN THE COVID ERA AND POST-COVID STAKES - Romdhane, Syrine Ben (International Journal of Accounting & Finance Review, 2021)
The spread of information technology and the digitalization of financial services raise a range of theoretical questions as the structures of the banking industry undergo change. This change has intensified with the impact of the COVID-19 pandemic which is already being observed. The purpose of this study is therefore threefold: (1) to analyze the impact of IT and the digitalization of financial services on the strategy and functioning of the pre-COVID-19 banking sector; (2) to study the challenges banks are facing in the COVID era in managing the crisis, and (3) to highlight post-COVID stakes. This study shows, on the one hand, that the crisis confirms the need for banks to combine physical proximity and digital offer, and on the other hand, that digitalization could be the solution for banks to consistently mitigate risks. Through this digital transformation and their ability to re-invent themselves, the banks would guard against potential similar crises. By adopting a more digitized and open behavior, they would be immune to such crises because they would have appropriate strategic plans, as they would be better equipped to counter the threats and better prepared to transform them into opportunities. JEL Classification Codes: B26, B41, G21, G32, O32.